Glucosamine‐grafted methacrylated gelatin hydrogels as potential biomaterials for cartilage repair. Issue 3 (1st August 2019) - Suo, Hairui; Li, Liang; Zhang, Chuanxin; Yin, Jun; Xu, Kedi; Liu, Jingyi; Fu, Jianzhong
Abstract: Glucosamine (GlcN) has been widely used to reduce joint pain and osteoarthritis progression, but the efficacy of GlcN remains controversial because of the low GlcN concentration reaching the articular cavity. The aim of this study is to provide an effective approach of GlcN delivery to a target site using photocrosslinkable methacrylated gelatin (GelMA)‐based hydrogels, where GlcN could be gradually released during the degradation of the GelMA hydrogel. Herein, GlcN was acrylated as the acryloyl glucosamine (AGA) and covalently grafted to GelMA, and more than 87.7% of 15% (w/v) GelMA hydrogel was grafted with AGA. Moreover, in vitro outgrowth and apoptosis assay of bone marrow stem cells (BMSCs) demonstrated that the GelMA–AGA hydrogels had better biocompatibility, larger cell attachment, and higher cell viability than pure GlcN and AGA materials. Also, 15% (w/v) GelMA–AGA hydrogel was injected into the defect site for in vivo rabbit cartilage repair. Compared with oral administration of pure GlcN and injection of pure GelMA, the repaired cartilages using GelMA–AGA hydrogels had the smoothest surface of the defect site, filling more than 95% defect bulk. The similar content of glycosaminoglycans to the native tissue and the maximum amount of type II collagen was found in the repaired cartilage using GelMA–AGA hydrogels, indicating the outgrowth of hyaline cartilage.